Ação formativa para elaboração de planos de aula na perspectiva do desenho universal para a aprendizagem no ensino médio - Silva, Jaudréia Ribeiro (Universidade Federal de São Carlos, 2024)
The great challenge of today's schools is to develop pedagogical practices that welcome diversity and pay attention to individual differences, promoting access with participation and successful retention of public students in Special Education (PAEE), thus achieving school inclusion. In secondary education, it is even more complex to promote teaching that meets the principles of inclusive education, given the structure and organization of this modality. Universal Design for Learning (UDL) emerges in this context with a theoretical approach that supports the flexibility of the curriculum through the diversification of teaching strategies, with a focus on diversity seeking to eliminate barriers to access to the common curriculum for all students. Considering this context, the general objective of this research was to analyze a Collaborative Training action for the development of lesson plans with UDL principles, by teachers in the Language area and the specialized educational service teacher in the context of high school. To this end, the study was organized in two stages, namely: Stage I - identifying the training need regarding aspects of training for inclusion, with the descriptive method. A semi-structured interview was used, individually, with nine teachers, two of whom were AEE teachers and seven teachers in the Language area, from a state school in a municipality in the interior of the state of Maranhão. This stage resulted in six thematic categories, namely: 1) teachers' perceptions about the inclusion of target audience students in special education; 2) teachers' perceptions about the relationship between teacher training and school inclusion; 3) teachers' perceptions about collaboration between the regular teacher and the Special Education teacher; 4) teachers’ perceptions about lesson planning; 5) teachers’ knowledge about Universal Design for Learning; 6) expectations about the Training Action. After qualitative analysis of the interviews, a collaborative Training Action was developed, based on the demands presented by teachers during the interview. In stage II, of the nine teachers, seven continued in the research, with the collaborative research design. Training meetings were held with the participants, with studies carried out on the themes of collaboration and AUD, discussions and reflections, focused on the demands of teachers and the school. An external study of the texts presented as references was proposed, in addition to written activities and videos. As a collaborative activity, teachers created and evaluated four lesson plans. There were six training meetings, all recorded on an audio recorder and transcribed in full for analysis. This stage resulted in five thematic categories, namely: 1) attitudinal challenges; 2) challenges for diversification in teaching strategies; 3) challenges of teaching work; 4) implications of UDL for lesson planning – teachers’ reflections; 5) preparation and evaluation of lesson plans based on the DUA – collaboration between teachers. The study showed that the perceptions that teachers have about inclusion and disability are still archaic and rigid, the result of negative conceptions about disability, which interferes with the way the teacher conducts teaching, producing barriers in the inclusion process, as well as barriers in the organizational structure of teaching. The Training Action on UDL, in the form of collaboration, showed training potential, as teachers were able to reflect on their own practice, as well as construct new ideas about inclusive pedagogical practices. It was possible to demonstrate that developing more accessible lesson plans based on the DUA is a challenge, given the conditions of teaching work that involve structure and appreciation of the teaching profession. On the other hand, it allowed working collaboratively, identifying new perspectives for school inclusion based on the DUA and collaborative practice between peers and special education teachers.
Training action to develop lesson plans from the perspective of universal design for learning in high school
Keywords: Educação especial; Desenho universal para a aprendizagem; Inclusão escolar; Planos de aula; Ensino médio; Special education; Universal design for learning; School inclusion; Lesson plans; High school; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO